Aplikasi T.R.U.S.T. ( The Recording Unit of Spy Tools ) pada Android - Reynaldo Suryo Purnomo; Andreas Handojo; Anita Nathania Purbowo (Jurnal Infra, 2016)
As the time goes, Spy Camera's types and functions will expand until it is divided into its functionality. Spy Camera can be found as one of spy tools to the people in different group of society for their safety and monitoring in various field; e. g records sounds, hidden camera for investigation, in finding specific evidence for cases, surveillance for store, houses, and can be used as a child-monitoring. With the improvement usability of Spy Camera, almost every houses or work places use Spy Camera in which we called CCTV (Closed Circuit Television). It functionality can be use as well for self-defense since these days we find it very hard to trust someone and it will need a large amount of money for buying an impractical spy camera. It triggered a necessity to build a cheap and practical Spy Camera with some amount of proper technological development, that necessity can be fulfilled. In this context, a smartphone technological development will be used because smartphone nowadays can be used for taking photos, record some videos, and even records sound. With a good Internet connection, an online backup could be performed with more features, which use motion sensor, an alarm, and data security. Finally, the application Spy Camera which we called T.R.U.S.T has various features such as taking pictures, records sounds, saving files and backing it up to Google Drive, sending emails, SMS trigger, and doing some general settings in taking pictures, video recording and application’s sounds.From above, it can be summarized that using smartphone features nowadays, a Spy Camera application can be made. A Spy Camera application is a solution for a cheap and practical Spy Camera. It doesn't need specific tools, but it can be used in today’s smartphones.